(untitled) - DEWANTORO, KRISSANDI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Increasingly grow and develop the company with the same kind of product cause the increasingly tight competition. In order to be able to deal with the competition, the company should have the efficient marketing strategies to offer its product to consumers. One of strategies is marketing mix consisting of product, price, promotion and place. The strategies also used by the Wisma Anisa Batik which able to influence the Tanjung Bumi batik purchasing decision. Viewing the phenomenon above the researcher interested to make a research of the marketing mix variable has effect on consumer decision in buying the Tanjung Bumi batik. The purpose of this research was to know the effect of marketing mix consisting of product, price, promotion and place on the decision of Tanjung Bumi Batik purchasing in Wisma Anisa Batik.This research used the primary data type while the sample taking technique used the accidental sampling method. Sample numbers used in this research were as many as 55 respondents constituting the Tanjung Bumi batik consumers in Wisma Anisa of Bangkalan Regency. Data analysis technique used in this research was using the multiple linear regression analysis.Of the result of research showed the regression coefficient number indicating that the Marketing Mix significantly influential on the purchasing decision in Wisma Anisa of Bangkalan regency. Key words: Product, Price, Promotion, Place, Purchasing decision